Handbook of Digital Homecare Successes and Failures - Bos, Lodewijk; Dumay, Adrie; Goldschmidt, Leonard; Verhenneman, Griet; Yogesan, Kanagasingam; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This second volume of the (3z(BHandbook of Digital Homecare(3y (Breviews the attempts to develop new ICT services for digital homecare, i.e. services to deliver, maintain and improve care in the home environment using the latest ICT technology and devices. The book highlights the successful projects as well as failures of Digital homecare and provides several (3z(Blessons learned(3y (Bto the wide audience of Health and ICT professionals.s
A high road to Dutch healthcare reform -- The Epilepsy Project in the Republic of Ireland: Lessons for Digital Homecare -- Care TV to support care delivery to independently living seniors -- Establishing an infrastructure for tele-care: combining the socio-technical and the clinical -- Screening and monitoring of elderly population for tele-ophthalmology in rural areas in -- Implementation of Mobile Computing in Canadian Homecare Programs: Project Risk Management and its Influence on Project Success -- AAL+: Continuous Institutional and Home Care Through Wireless Biosignal Monitoring Systems -- Home medication management by videophone; translation from pilot project to integrated service.-The introduction of activity monitoring as part of care delivery to independently living seniors.-The SAPHIRE Project: A Retrospective View on the Homecare Scenario -- An Intelligent Multi-Agent Memory -- About motivated project teams, user expectations, proof-of-concept testing and the after-a-good-project-hang-over.
Keywords: Engineering; Health informatics; Application software; Biomedical engineering; Engineering; Biomedical Engineering; Computer Appl. in Social and Behavioral Sciences; Health Informatics; Electronic books